2008
DOI: 10.1038/labinvest.2008.19
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the HER2/TOP2A amplicon in breast cancer and breast cancer cell lines

Abstract: HER2 and TOP2A are targets for the therapeutic agents trastuzumab and anthracyclines and are frequently amplified in breast cancers. The aims of this study were to provide a detailed molecular genetic analysis of the 17q12-q21 amplicon in breast cancers harbouring HER2/TOP2A co-amplification and to investigate additional recurrent co-amplifications in HER2/ TOP2A-co-amplified cancers. In total, 15 breast cancers with HER2 amplification, 10 of which also harboured TOP2A amplification, as defined by chromogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
154
2
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 138 publications
(174 citation statements)
references
References 45 publications
(93 reference statements)
9
154
2
9
Order By: Relevance
“…Copy number changes were categorized as gains, losses or amplifications according to previously validated thresholds for each clone. 15 Threshold values were chosen to correspond to three standard deviations of the normal ratios obtained from the filtered clones mapping to chromosomes 1-22, assessed in multiple hybridizations between DNA extracted from a pool of male and female blood donors as previously described 16,17 (Log2 ratio of ±0.12). Low-level gain was defined as a smoothed Log2 ratio of between 0.12 and 0.45, corresponding to approximately 3-5 copies of the locus, whereas gene amplification was defined as having a Log2 ratio 40.45, corresponding to more than five copies.…”
Section: Microarray Comparative Genomic Hybridizationmentioning
confidence: 99%
“…Copy number changes were categorized as gains, losses or amplifications according to previously validated thresholds for each clone. 15 Threshold values were chosen to correspond to three standard deviations of the normal ratios obtained from the filtered clones mapping to chromosomes 1-22, assessed in multiple hybridizations between DNA extracted from a pool of male and female blood donors as previously described 16,17 (Log2 ratio of ±0.12). Low-level gain was defined as a smoothed Log2 ratio of between 0.12 and 0.45, corresponding to approximately 3-5 copies of the locus, whereas gene amplification was defined as having a Log2 ratio 40.45, corresponding to more than five copies.…”
Section: Microarray Comparative Genomic Hybridizationmentioning
confidence: 99%
“…Owing to the high level of coordinated genetic aberrations within this region, it may prove challenging to pinpoint the gene(s) responsible for driving the response to chemotherapeutic agents. HER2 is the most recognized and studied gene within the region, with amplification of HER2 being associated with amplifications and deletions of neighbouring genes including GRB7, RARA, THRA1, CDC6 and TOP2A (Arriola et al, 2008). It has recently been shown that the patterns of coordinated genetic aberrations are inconsistent between HER2-amplified tumours (Arriola et al, 2008).…”
Section: Chromosome 17mentioning
confidence: 99%
“…HER2 is the most recognized and studied gene within the region, with amplification of HER2 being associated with amplifications and deletions of neighbouring genes including GRB7, RARA, THRA1, CDC6 and TOP2A (Arriola et al, 2008). It has recently been shown that the patterns of coordinated genetic aberrations are inconsistent between HER2-amplified tumours (Arriola et al, 2008). However, Arriola et al (2008) only considered 19 HER2-amplified tumours and did not consider genetic alterations in HER2 non-amplified tumours.…”
Section: Chromosome 17mentioning
confidence: 99%
See 2 more Smart Citations